A coupled CFD-DEM simulation of upward seepage flow in coarse sands. Issue 5 (28th May 2019) - Ma, Zhe; Wang, Yin; Ren, Nianxin; Shi, Wei
Abstract: The suction anchor becomes more popular for offshore oil and gas industry in deeper water. For suction anchor–soil interaction, the prediction of hydraulic conductivity of porous materials is a long-standing problem in offshore engineering. To investigate the hydraulic characteristics, an upward seepage flow through saturated sands is considered in this study. A numerical approach, which is able to describe the fluid–particle interaction at particle scale, has been employed to analyse fluid flow in sands. This approach is constructed by adopting a coupled discrete element method and computational fluid dynamic approach (CFD-DEM numerical model). The coupled CFD-DEM approach is first benchmarked by a classic geomechanics problem where analytical solutions are available, and then employed to investigate the characteristics of upward seepage flow in coarse sand columns. Through numerical modelling, the predicted relation between hydraulic gradient and flow velocity is obtained and it is compared with the classical analytical correlation. The effect of several bulk and micromechanical parameters including packing porosity, particle size combination and inter-particle rolling resistance on the flow characteristics is numerically examined. The results show that the particle polydispersity and packing porosity have significant effect on the hydraulic conductivity in the seepage flow. The introduction of inter-particle rolling resistance can change initial packing structure of particle assembly in some extent rather than the hydraulic conductivity from the particle shape effect perspective. A further development of numerical model, in which the effect of non-spherical particles on the seepage flow, will be carried out later.